2021
DOI: 10.1111/jgh.15574
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Safety of vedolizumab during pregnancy in patients with inflammatory bowel disease

Abstract: Background and Aim: Vedolizumab is a novel monoclonal antibody used in patients with inflammatory bowel disease, often affecting women of child-bearing age. We aimed to compare maternal and fetal adverse outcomes in pregnancies of women with inflammatory bowel disease exposed to vedolizumab versus those on other treatment. Methods: We performed a systematic literature search through December 2020 looking for studies including outcomes from pregnancies of female inflammatory bowel disease patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, a 2021 meta-analysis that included four studies in mothers exposed to vedolizumab suggested an increase in the odds of adverse pregnancy outcomes (OR 2.18, 95% CI 1.52-3.13) [112]. But both this study and a previous 2020 vedolizumab safety re-view concluded that disease activity, rather than medication, is likely the main factor in adverse outcomes among patients receiving anti-integrin therapy [113,114].…”
Section: Anti-integrins: Vedolizumabmentioning
confidence: 61%
“…However, a 2021 meta-analysis that included four studies in mothers exposed to vedolizumab suggested an increase in the odds of adverse pregnancy outcomes (OR 2.18, 95% CI 1.52-3.13) [112]. But both this study and a previous 2020 vedolizumab safety re-view concluded that disease activity, rather than medication, is likely the main factor in adverse outcomes among patients receiving anti-integrin therapy [113,114].…”
Section: Anti-integrins: Vedolizumabmentioning
confidence: 61%
“…There was no evidence for an increased signal for placental complications in the VDZ-exposed cohort despite speculation regarding potential interference of VDZ with placental development. A meta-analysis comparing adverse pregnancy-related events in VDZ-exposed patients with disease-matched controls yielded 213 VDZ-exposed pregnancies from 4 studies and found an increase in overall adverse pregnancy–related outcomes including preterm birth and early pregnancy loss (25). On the contrary, a literature review of all publications until November 2019 yielded 5 unique studies with 284 VDZ-exposed pregnancies and found no evidence for safety concerns in the individual studies and on cumulative assessment (26).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of vedolizumab, complications such as premature rupture of membranes, pre-eclampsia, abortion, and stillbirths have been reported in up to 25% of pregnancies and neonatal complications, including prematurity, intrauterine growth retardation, and congenital malformations in up to 35% of infants from mothers exposed to the medication. [ 2 ] A more recent study [ 13 ] confirmed an increase in unfavorable outcomes, such as premature births and spontaneous abortions in pregnant women taking vedolizumab, but the results may be related to disease activity. The same results were seen in a recently published meta-analysis, [ 14 ] in which the prevalence of early pregnancy loss and preterm birth were higher in vedolizumab vs anti-TNF users.…”
Section: Discussionmentioning
confidence: 99%